2017
DOI: 10.1186/s40001-017-0257-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c and risk of left atrial thrombus and spontaneous echo contrast in non-valvular atrial fibrillation patients

Abstract: ObjectivesTo evaluate the relationship between hemoglobin A1c (HbA1c) and risk of left atrial thrombus/spontaneous echo contrast (LAT/SEC) in non-valvular atrial fibrillation (AF) patients.MethodsIn this retrospective study, 1158 consecutive non-valvular AF patients undergoing transesophageal echocardiography prior to radiofrequency catheter ablation or electric cardioversion were enrolled. Baseline characteristics were collected and analyzed.ResultsThere were 87 (7.5%) patients with LAT/SEC. The HbA1c levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Combined with comb-like structures of LAA, reduced LAAV is easy for thrombus formation. Ren [13] found that elevated HbA1c indicated a significantly increased risk for left atrial thrombus/spontaneous echo contrast in nonvalvular AF patients. Furthermore, LA/LAA thrombus is a potential source of thromboembolic events such as ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with comb-like structures of LAA, reduced LAAV is easy for thrombus formation. Ren [13] found that elevated HbA1c indicated a significantly increased risk for left atrial thrombus/spontaneous echo contrast in nonvalvular AF patients. Furthermore, LA/LAA thrombus is a potential source of thromboembolic events such as ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Left atrial appendage is a significant thrombus formation source in more than 90% of patients with nonvalvular AF. [7][8][9] Left atrial appendage closure (LAAC) has been demonstrated as an important alternative to prevent stroke for AF patients, especially for those intolerant to oral anticoagulation drugs. 10,11 AF ablation provides relatively reliable rhythm control, and LAAC reduces the risk of stroke.…”
Section: Introductionmentioning
confidence: 99%